The Free Mind : A Lateral Thinking Approach - Edward De Bono (Jaico Publishing, 2008)
Edward de Bono believes in freedom, but he poses the question: If you cannot see clearly, are you making a free choice? That question is at the heart of his new book. De Bono has devoted his life and career to getting his readers business leaders, educators, and politicians among others to understand that clarity of thinking is essential to a free society. It is not enough to simply be free from coercion. De Bono argues that there is no true freedom without the ability to see correctly the options we have. And, to see these options requires thinking thinking of a kind that De Bono says is not the norm and which urgently needs to be emphasized and taught.The best short introduction to his work, The Free Mind uses anecdote to convey his ideas and provides numerous examples that illustrate his thesis: to be free means to understand the choices we make, and this understanding can only come through improving the way we think.